Variação sazonal da composição do óleo essencial de Myrcia salzmannii Berg. (Myrtaceae) Seasonal variation of the composition of essential oil from Myrcia salzmannii Berg. (Myrtaceae) - Martins Dias de Cerqueira; Edson de Jesus Marques; Dirceu Martins; Nídia F. Roque; Frederico Guaré Cruz; Maria Lenise da Silva Guedes (Química Nova, 2009)
This work report the seasonal variation of composition of the volatile oils from leaves and from flowers of Myrcia salzmannii harvested in the sand dunes of Salvador, Bahia, northeastern region of Brazil in the years 2001 and 2003. The oils were analyzed by GC-FID and GC-MS being identified 49 components. Nine essential oil samples of leaves collected on different months and years and one sample of flowers were analyzed. β-Caryophyllene and α-humulene were the only compounds present in all of the samples being the first the majority compound.